(untitled) (Research, Society and Development, 2022)
Death is a future and certain biological event, facing the finitude of life can be difficult for a large number of people to accept, because it announces the end of the existential experiences of a given individual, in this context among the various issues addressed within bioethics in medicine that seek clarification, death is one of them. Thus, the present research aimed to analyze the knowledge of medical students about bioethical principles at the end of life. This is an observational and descriptive study that was carried out using an online questionnaire to assess the knowledge of medical students at the Uninovafapi University Center regarding bioethics at the end of life, the assessment was carried out via Google Forms ®, to minimize any risk of embarrassment and contagion for the participants, the sample used was calculated over the 198 students between the 9th and 12th periods, totaling 131 volunteers. The results were tabulated and analyzed using Excel. Results: Most students attending the 11th of the course, having no previous contact with the subject in question, thus observing a divergence in the results regarding the actions that must be taken in the situations presented during the questionnaire, for all the principles exposed, these being that of autonomy, beneficence, veracity, proportionality and double effect. In conjunction with these principles, I will analyze the contact with students to advance will directives, which had never been performed by any of the participants, as well as they chose analgesia and venous hydration as the most accepted care and treatments.